2022
DOI: 10.1136/bmj-2021-069155
|View full text |Cite
|
Sign up to set email alerts
|

Validity of data extraction in evidence synthesis practice of adverse events: reproducibility study

Abstract: ObjectivesTo investigate the validity of data extraction in systematic reviews of adverse events, the effect of data extraction errors on the results, and to develop a classification framework for data extraction errors to support further methodological research.DesignReproducibility study.Data sourcesPubMed was searched for eligible systematic reviews published between 1 January 2015 and 1 January 2020. Metadata from the randomised controlled trials were extracted from the systematic reviews by four authors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…The studies used for data extraction in the two groups will be identified before the start of the trial, based on our previous well-established database of meta-analyses of adverse events (binary outcomes) [7]. The database covers 201 systematic reviews of randomized controlled trials with 829 meta-analyses with pharmaceutical or non-pharmaceutical interventions, and all the meta-analytical data in the database have been carefully checked for their validity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies used for data extraction in the two groups will be identified before the start of the trial, based on our previous well-established database of meta-analyses of adverse events (binary outcomes) [7]. The database covers 201 systematic reviews of randomized controlled trials with 829 meta-analyses with pharmaceutical or non-pharmaceutical interventions, and all the meta-analytical data in the database have been carefully checked for their validity.…”
Section: Methodsmentioning
confidence: 99%
“…Systematic review and meta-analysis has been one of the most important sources of evidence and thus the validity of such evidence directly determines the reliability and quality of healthcare administration [2]. Unfortunately, in real-world, the evidence generated from systematic reviews and meta-analyses is far from valid or trust-worthy due to a multiple reasons, where one of which would be errors during data extraction -as recorded in previous studies, as much as 85% of the systematic reviews faces serious issue in data reproducibility [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The “no-humbug” expression used by Dr. Warren was not a surprising choice. We must think about innovations consolidated by evidence-based care and rigorous scientific studies to avoid dire consequences that can put patients at risk (Slayton et al 2018; Howick et al 2022; Xu et al 2022), such as the failing protoplast/Teflon implants in the 1980s and 1990s that highly affected thousands of lives of patients with temporomandibular disorders (Lee et al 2018). There is great potential to be more integrated than ever with patients and their other care providers via devices and combining medical and dental electronic health records.…”
Section: Introductionmentioning
confidence: 99%